Pengaruh Return On Assets (ROA), Return On Equity (ROE), Earning Per Share (EPS) dan Debt to Equity Ratio (DER) Terhadap Harga Saham - Tania Audinawati Br Tarigan; Menik Indrati (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This research aims to analyze the influence of Return On Assets (ROA), Return On Equity (ROE), Earning Per Share (EPS), and Debt to Equity Ratio (DER) on share prices in 34 LQ45 index companies during 2018–2020. The research method used is associative with the population of companies listed on the LQ45 index of the Indonesian Stock Exchange. Data collection was carried out through annual financial reports from 34 companies during the 2018-2020 period. The sampling method uses purposive sampling with certain criteria, and data analysis is carried out using multiple linear regression using SPSS software. The research results show that these four variables simultaneously influence stock prices. Specifically, Earning Per Share (EPS) has a positive influence, while Debt to Equity Ratio (DER) has a negative influence. Return On Assets (ROA) and Return On Equity (ROE) do not have a significant effect on stock prices.